SISTEM PERIWAYATAN AHLI HADIS DAN AHLI SEJARAH: Kajian Perbandingan antara Aḥmad ibn Ḥanbal dan Muḥammad ibn Isḥāq dalam Riwayat Perang Uhud - Aenul Yaqin (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2021)
This article discusses the differences between the narration systems of hadith experts and historians. The figure who represents the hadith expert is Aḥmad ibn Ḥanbal and the figure who represents the historian is Muḥammad ibn Isḥāq. The case being compared is the history of the Uhud war. The results of this article show that hadith experts are very concerned about the chain of transmission, while historians pay attention to matn or stories.